Features and performance of edible films, obtained from whey protein isolate formulated with antimicrobial compounds - Ramos, Óscar L.; Silva, Sara I.; Soares, José C.; Fernandes, João C.; Poças, M. Fátima; Pintado, Manuela E.; Malcata, F. Xavier (Food research international, 2012)
The goal of this research effort was to assess the efficacy of edible films produced from whey protein isolate (WPI) and glycerol, including incorporation of lactic acid (LA) and propionic acid (PRO), chitooligosaccharides with nominal MW of 3kDa (COS) and natamycin (NA) as antimicrobial agents. Their features were evaluated in vitro via agar diffusion and viable cell counting, against spoilage microflora often found contaminating cheese surfaces. The effect of incorporating the aforementioned compounds upon thickness, moisture content (MC), solubility (S), density (ρs), water activity (aw) and water vapor permeability (WVP), as well as upon tensile and optical properties of those films were also evaluated. Films formulated with LA, PRO or COS exhibited antimicrobial activity against all microorganisms tested, yet the viable cell count assay was more sensitive and reproducible. COS was the most active against Gram-negative bacteria, whereas LA was the most active against Gram-positive ones. NA was not active against bacteria, but displayed the strongest effect against yeasts. Incorporation of said antimicrobial compounds did not significantly (p>0.05) affect film thickness, yet it significantly (p<0.05) reduced tensile strength (TS). Incorporation of LA and NA in particular did not significantly (p<0.05) affect MC, S, ρs, WVP, elongation at break (EB) and Young's modulus (YM) values; however, a statistically significant increase (p<0.05) of MC, S and WVP, together with a statistically significant decrease (p<0.05) of ρs were attained upon incorporation of PRO or COS. Moreover, PRO produced the highest variation (p<0.05) in EB, TS and YM, whereas COS produced the highest change (p<0.05) in optical properties. ► Antimicrobial efficacy of additives to whey-protein based edible films was tested. ► Effects of said additives upon mechanical and optical properties were assessed. ► Chitooligosaccharide (COS) was strongest against Gram-negative bacteria. ► Lactic acid was strongest against Gram-positive bacteria. ► COS produced the highest change in optical properties.